Knowledge and Practices of Students Regarding the Use of Face Masks to Limit the Spread of Coronavirus Disease (COVID-19) - Burhan Izzaddin Sabir; Shahab Ahmad Sideeq; Yousif Baker Omer; Nasir Khadir Khalaf; Sideeq Sadir Ali (Hawler Medical University, 2022)
Background and Objectives: Many countries are implementing face masks as part of their pandemic prevention strategies. Because the virus is so widespread, incorrect usage and disposal of masks can increase the transmission rate. The purpose of this study was to assess knowledge and practices of students in wearing facemask to prevent the spread of the new coronavirus (COVID-19). Methods: A cross-sectional descriptive study of 365 undergraduate students at Hawler Medical University was conducted from June 15th to October 15th, 2021. The data was gathered through direct interviews using a questionnaire that had been modified include demographic information, ten questions about knowledge, and 17 questions about practices for using surgical face masks to reduce COVID-19 exposure. Result: The result revealed that highest percentage of students were 18 to 20 years old (66.6%). Most of the participants in this study were female (59.5%). Participants demonstrated fair knowledge (N=218, 59.7%). Concerning the using surgical facemask to prevent the spread of COVID-19 and good practical knowledge (N=273, 74.8%). The highest levels of practical knowledge were related to wearing face masks in hospital premises to protect against COVID-19 (91.8%) and wearing masks in public spaces to protect against COVID-19 (87.1%). Conclusion: The studied students had a poor understanding of how to utilize face masks. Enhancing one's knowledge and appropriate use of face masks takes time and effort. It is necessary to implement massive education campaigns at the level of Hawler Medical University to increase the proportion of knowledge about COVID-19 and stop its spread.